Nitrogen management in guava (Psidium guajava L) cv. Lucknow-49 through fertigation under north Gujarat conditions (Indian Journal of Arid Horticulture, 2025)
Guava (Psidium guajava L.) is an important one of the fruit crop of North Gujarat. Though it is grown in arid and semi-arid conditions, it responds well to nitrogen and farmers apply nitrogen in two splits in the month of June and September. Recently, drip irrigation system gets the prime position for efficient use of water and fertilizer. How- ever, regular irrigation is essential during the reproductive phase (i.e. flowering to ripening of fruits) as irregular mois- ture conditions causes dropping of flowers and small fruits (Patil et al., 2002). Among different management practices, fertigation plays an important role for enhancing yield and quality of product with saving of water and efficient use of fertilizer. Water is a limiting factor in the arid regions. The fertilizers are becoming costlier day by day. There fore, even under these constraints, it is essential to utilize both these inputs on the scientific basis to get a remunerative crop. Drip system increases the growth and nutritional sta- tus of pomegranate under the salt affected soils. (Dwivedi et al, 1996) by leaching out excess salt and maintaining proper concentration through continuous dropping of water. This system also checks seepage and evaporation loses. (Varsney et al. 1993). However, there is no informa- tion available on the effect of fertigation on this fruit crop under North Gujarat conditions. There fore the present study was undertaken to generate information on the above aspects.
Keywords: fertilizer; leaching; drip irrigation system; remunerative crop